High DMBT1 concentrations in breast milk correlate with increased risk of infection in preterm and term neonates - Ronellenfitsch, Sebastian Helmut; Weiß, Christel; Frommhold, David; Koch, Lutz; Mollenhauer, Jan; Pöschl, Johannes; Müller, Hanna (BMC pediatrics, 2012)
Human milk contains immune molecules involved in the protection of newborns against infections. We analyzed the concentration of Deleted in Malignant Brain Tumors 1 (DMBT1), a protein with functions in innate immunity, in breast milk.